FREQUENCY AND RISK FACTORS OF MICROSCOPIC COLITIS AS A CAUSE OF CHRONIC WATERY DIARRHOEA - Sabhita Shabir Shaikh,; Khalid, Raheela; Bukhari, Uzma; Shaikh, Hafeezullah; Ijtaba Rizvi , Syeda Aamna; Shabbir, Alveena (Journal of Ayub Medical College Abbottabad, 2023)
Background: Microscopic colitis (MC) is one of the most underdiagnosed conditions leading to chronic watery diarrhoea in patients worldwide. This is the first study of this kind in Pakistan and we aimed to calculate the frequency as well as study the risk factors behind the disease. Methods: This was a prospective cross-sectional study in a tertiary care hospital in Pakistan. A total of 58 participants with chronic watery diarrhoea who had normal colonoscopy were recruited for the study and biopsies were obtained for diagnosing MC. Results: 2 participants out of 58 (3.4%) had biopsy proven microscopic colitis; one patient had a lymphocytic colitis variant and the other had a collagenous colitis variant. The average score based on the MC scoring system was 7.53 in the entire study group. The patient with lymphocytic colitis had a score of 06 while the patient with collagenous colitis had a score of 8. Conclusion: The frequency of microscopic colitis was found to be 3.4% of all cases of chronic watery diarrhoea. A link between MC and autoimmune diseases was also observed. However, we had a limited sample size and encourage future studies to employ a larger sample size in order to get a multifaceted look at the disease process.